1989
DOI: 10.1016/0014-5793(89)80217-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrostimulation‐induced increases in fatty acid‐binding protein and myoglobin in rat fast‐twitch muscle and comparison with tissue levels in heart

Abstract: Chronic stimulation of rat fast-twitch muscle increased the content of both fatty acid-binding protein (FABP) and myoglobin. The increases in FABP, which reached values close to that of cardiac muscle, exceeded those in myoglobin and those in citrate synthase and 3-hydroxyacyl-CoA dehydrogenase activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 15 publications
5
18
0
Order By: Relevance
“…A chronic increase in contractile activity and a shift to oxidative muscle metabolism would require a higher demand in oxygen and fuel supply in the form of fatty acids. Consequently the drastic increase in the oxygen-transporter myoglobin, the intracellular fatty acid binding protein FABP-3 and the extracellular fatty acid transporter albumin strongly indicates that these three central metabolic regulators could function as limiting factors of oxidative metabolism in fast fibres [40,63]. The findings from our DIGE analysis clearly establish the small cytosolic FABP-3 protein as a suitable biomarker of muscle fibre type shifting.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…A chronic increase in contractile activity and a shift to oxidative muscle metabolism would require a higher demand in oxygen and fuel supply in the form of fatty acids. Consequently the drastic increase in the oxygen-transporter myoglobin, the intracellular fatty acid binding protein FABP-3 and the extracellular fatty acid transporter albumin strongly indicates that these three central metabolic regulators could function as limiting factors of oxidative metabolism in fast fibres [40,63]. The findings from our DIGE analysis clearly establish the small cytosolic FABP-3 protein as a suitable biomarker of muscle fibre type shifting.…”
Section: Discussionmentioning
confidence: 66%
“…An elevation of aerobic-oxidative capacity, decreased fibre calibre and changes in the density of distinct muscle proteins, switches in isoform expression patterns and alterations in proteinprotein interactions are established biochemical and cell biological hallmarks of transformed skeletal muscles. This includes: (i) metabolic pathways such as the citric acid cycle, fatty acid oxidation and the respiratory chain which causes a drastic increase in enzymes of aerobic substrate oxidation [39,40], (ii) the contractile apparatus that undergoes a stepwise replacement of myosin light and heavy chains from fast isoforms to their slower counterparts [41,42], (iii) the ion-regulatory machinery of the excitation-contractionrelaxation cycle with a shift from fast to slower isoforms with respect to the SERCA-type Ca 21 -ATPases, the voltagesensing dihydropyridine receptor, the ryanodine receptor Ca 21 -release channel and various Ca 21 -binding proteins [43,44], (iv) the neuromuscular junction with distinct changes in the acetylcholinesterase and the nicotinic acetylcholine receptor [45,46] and, (v) a decrease in the supramolecular interaction pattern between Ca…”
Section: Introductionmentioning
confidence: 99%
“…That a metabolic switch takes place in senescent muscles is supported by the finding that the fatty acid-binding protein FABP and the oxygen carrier myoglobin are increased during aging . Both proteins have previously been established as limiting factors of aerobic-oxidative metabolism in slow-twitching fibres (Kaufmann et al, 1989). Thus, both changes in contractile kinetics and metabolic adaptations suggest an age-related switch to a slower muscle type.…”
Section: Discussionmentioning
confidence: 93%
“…Representative examples of stimulation-induced changes in major muscle proteins is the stepwise replacement of myosin heavy chains from the MHCII isoforms to MHCI [14], a shift from the fast SERCA1 isoform of the sarcoplasmic reticulum Ca 2+ -ATPases to the slower SERCA2 isoform [15], the increase in the levels of the a-and ysubunits of the nicotinic acetylcholine receptor [12] and the gradual increase in the activity of enzymes involved in the main metabolic systems of aerobic substrate oxidation, i.e., the citric acid cycle, fatty acid oxidation and the respiratory chain [11,16,17]. The recent blot overlay analysis of the sarcoplasmic reticulum Ca 2+ -binding protein calsequestrin, using a peroxidase conjugate probe, revealed that the fast-toslow transition process triggers a distinct reduction in fast calsequestrin and a concomitant alteration in calsequestrin interactions with the ryanodine receptor Ca 2+ -release channel [13].…”
Section: Introductionmentioning
confidence: 99%